Respostas

2014-05-25T17:08:18-03:00
X(x+9)+x+9=0

Aplicando distributiva -> x²+9x+x+9=0

Tal que... x²+10x+9=0
a=1
b= 10
c=9

delta= b²-4ac -> 10²-4x1x9= 100-36=64

BHASKÁRA
-b+-raiz quadrada de delta sobre 2a

Tal que...
x'= -10+8/2= -2/2= -1
x''= -10-8/2= -18/2= -9
2014-05-25T17:10:10-03:00
x(x+9)+x+9=0
x(x+9) = x^2 + 9x + x + 9
= x^2 + 10x + 9
a= 1
b= 10
c = 9
Δ = b^2 - 4acΔ = 10^2 - 4 × 1 × 9
Δ = 100 - 36
Δ = 64
x = -b+/- √Δ
     -------------
         2a
x = -10+/- √64 ÷ 2 × 1
x = -10+/- 8 ÷ 2
x' = -10 + 8 ÷2 = 1
x''= -10 - 8 ÷2 = -9